Cyclobutane and Cyclobutene Synthesis: Catalytic Enantioselective [2+2] Cycloadditions. Issue 41 (2nd September 2015) - Xu, Yao; Conner, Michael L.; Brown, M. Kevin
Abstract Cyclobutanes and cyclobutenes are important structural motifs found in numerous biologically significant molecules, and they are useful intermediates for chemical synthesis. Consequently, [2+2] cycloadditions to access cyclobutanes and cyclobutenes have been established to be particularly useful transformations. Within the last 10 years, an increase in the frequency of publications for catalytic enantioselective [2+2] cycloadditions has occurred. These reactions provide access to a wide array of enantiomerically enriched chemical diversity that was not previously attainable. Described in this review are the advances made in catalytic enantioselective [2+2] cycloadditions to access cyclobutanes and cyclobutenes.